1989
DOI: 10.1002/syn.890040410
|View full text |Cite
|
Sign up to set email alerts
|

Autoradiographic quantification of serotonin1A receptors in rat brain following antidepressant drug treatment

Abstract: There is growing evidence that the serotonergic (5-HT) system is involved in the pathogenesis and treatment of major depression. The 5-HT receptor subtype involved in the enhancing effect of antidepressant treatments, however, has not been identified. The present study was undertaken to quantify 5-HT1A sites in the rat brain by autoradiography and membrane binding, using the selective ligand [3H]8-hydroxy-N,N-dipropyl-2-aminotetralin (8-OH-DPAT), following long-term antidepressant treatment. Following a 21-day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
1
2

Year Published

1992
1992
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(74 citation statements)
references
References 44 publications
8
63
1
2
Order By: Relevance
“…The most likely interpretation for this effect is that reuptake blockade, by increasing the intrasynaptic availability of 5-HT, results in a greater activation of terminal autoreceptors, which in turn, reduce the amount of released 5-HT. Autoradiographic studies showed that repeated doses of fluoxetine did not change the density of 5-HT1A receptors in the rat hippocampus, but amitriptyline increased the number ofthose sites (Welner et al 1989). The present results show an increase in the 5-HTIA receptor density in the hippocampus, which represents post-synaptic binding sites (Hamon et al 1987), after repeated treatment with most ofthe tested compounds.…”
Section: Discussionsupporting
confidence: 56%
“…The most likely interpretation for this effect is that reuptake blockade, by increasing the intrasynaptic availability of 5-HT, results in a greater activation of terminal autoreceptors, which in turn, reduce the amount of released 5-HT. Autoradiographic studies showed that repeated doses of fluoxetine did not change the density of 5-HT1A receptors in the rat hippocampus, but amitriptyline increased the number ofthose sites (Welner et al 1989). The present results show an increase in the 5-HTIA receptor density in the hippocampus, which represents post-synaptic binding sites (Hamon et al 1987), after repeated treatment with most ofthe tested compounds.…”
Section: Discussionsupporting
confidence: 56%
“…Welner et al (1989) observed a reduction in the dorsal raphe and decreased binding in midbrain was observed by Li et al (1994) after chronic fluoxetine. Changes have been reported by some authors in the hippocampus but are inconsistent, showing increased density (Klimek et al 1994) or decreased density and increased affinity (Maj et al 1996).…”
Section: Serotonergic Receptors Of the 5-ht 1a Subtype Have Been Suggmentioning
confidence: 82%
“…It should be emphasized that both observations (change in receptor sensitivity and unchanged density) have been obtained in the same animals. Previous work with SSRIs and selective 5-HT 1A agonists is inconclusive in regards to the ability of these agents to down-regulate the density of raphe 5-HT 1A autoreceptors after chronic (2-3 weeks) treatments (Welner et al 1989;Hensler et al 1991;Fanelli and McMonagle-Strucko 1992;Casanovas et al 1999a;Le Poul et al 1999), whereas there is convincing evidence on their ability to induce a functional desensitization de Montigny 1987, 1994;Hensler et al 1991;Invernizzi et al 1994;Casanovas et al 1999a; see however Sharp et al 1993).…”
Section: Discussionmentioning
confidence: 99%